PRINCIPLES CHARACTERISTIC OF NOVELS IN THE CONTEMPORARY LITERARY PROCESS - Rohila Xo‘janazarova (The Conference Hub, 2025)
The article analyzes the main principles of the novel genre in the contemporary literary process. Issues such as realism and lifelikeness, artistic psychologism, the conflict between the individual and society, elements of modernism and postmodernism, the harmony of national and universal values, the renewed interpretation of the protagonist, and formal freedom are discussed.
Keywords: novel, realism, artistic psychologism, individual and society, modernism, national identity